Effectiveness of Intravitreal Bevacizumab in Various Ocular Diseases - Khwaja Sharif ul Hasan, Adnan Afaq, Erum Shahid (Pakistan Journal of Ophthalmology, 2018)
Purpose: To evaluate the efficacy of monthly intravitreal bevacizumab injections (1.25 mg/.05 ml) in improving or stabilizing visual outcomes measured by Snellen’s visual acuity charts for diverse ocular diseases. Material and Methods: This was a prospective hospital based study in which a total number of 108 eyes of 80 patients were included with various ocular diseases. Maximum three intravitreal bevacizumab injections 1.25mg in 0.05ml each was given over a period of 3 months and follow up for 06 months after the first injection was carried out. The criteria for improvement was a gain of at least one line on Snellen’s visual acuity chart, compared to the baseline while stabilization was considered if the visual acuity was unchanged relative to the baseline. Results: A total number of 108 eyes of 80 patients were included in the study. Males were 40 and females were also 40 with an age range of 32-70 years. They were subjected to intravitreal injection of bevacizumab. Ten eyes (62.5%) with neovascular age related macular degeneration (ARMD) showed improvement while visual acuity was stabilized in 06 eyes (37.5%). In diabetic macular edema (DME) 30 eyes (68.1%) showed improvement, 10 eyes (22.7%) were stabilized and in 04 eyes (9%) visual loss continued. In patients with proliferative diabetic retinopathy (PDR) with vitreous hemorrhage 30 eyes (93.7%) showed improvement while stabilization of visual acuity was noted in 02 eyes (6.2%). In central retinal venous occlusion (CRVO) 04 eyes (80%) showed improvement and stabilization occurred in 01 eye (20%). Out of the 08 eyes of branch retinal venous occlusion (BRVO) all eyes showed visual improvement (100%). All 03 eyes (100%) of myopic choroidal neovascular membrane (CNV) patients also showed improvement. No systemic side effects of the given treatment were observed. Conclusion: The treatment with Bevacizumab is beneficial in improving and stabilizing visual acuity not only in neovascular ARMD but also in other chorioretinal vascular disorders.